Interventions Promoting Physical Activity Among Older Adults: A Systematic Review and Meta-Analysis - Grande, Guilherme D. [UNESP] (2020)
Background and Objectives: Frequent participation in physical activity (PA) has benefits across the lifespan but is particularly important for older adults. PA levels are either measured by objective or self-reported survey methods. Objective PA measurement is used to increase accuracy. This systematic review investigated the effect of physical activity-based interventions on objectively measured PA levels among community-dwelling adults aged 60 years and older. Research Design and Methods: Literature searches were conducted in five electronic databases and four clinical trial registries. Randomized controlled trials investigating the effect of physical activity-based interventions on objectively measured PA levels (e.g., accelerometers or pedometers) in community-dwelling adults aged 60 years and older compared with no/minimal intervention were considered eligible. Data were pooled using the most conservative estimates reported from each study using the standardized mean difference (SMD). Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to evaluate the overall quality of the evidence. Results: Fourteen published trials and 3 ongoing trials were identified. There were significant effects favoring physical activity-based interventions compared with minimal intervention at short-term (less than or equal to 3 months) (SMD: 0.30, 95% CI: 0.17 to 0.43) and intermediate-term (more than 3 months and less than 12 months; SMD: 0.27, 95% CI: 0.06 to 0.49) follow-ups. The quality of evidence was moderate according to GRADE (downgraded for risk of bias). Discussion and Implications: Our findings suggest that physical activity-based interventions may increase objectively measured PA levels in community-dwelling older adults. Further studies are still needed to identify the optimal dose, intensity, and mode of delivery of physical activity-based interventions.